Alzheimer’s disease and epilepsy: The top 100 cited papers - Zhang, Gui-Fen; Gong, Wen-Xin; Xu, Zheng-Yan-Ran; Guo, Yi (Frontiers in Aging Neuroscience, 2022)
Background: Alzheimer's disease (AD) is one of the common neurodegenerative diseases, which often coexists with epilepsy. It is very significant to study the treatment options and the relationship between AD and epilepsy. Aims The purpose of this study was to analyze the top 100 cited papers about AD and epilepsy using bibliometrics, and to describe the current situation and predict research hot spots. Methods: Top 100 papers were obtained from the Web of Science Core Collection (WoSCC). The WoSCC was used to analyze the author, institution, country, title, keywords, abstract, citation, subject category, publication year, impact factor (IF), and other functions. SPSS25 software was used for statistical analysis and CiteSpace V.5.7.R2 was used to visualize the information through collaborative networks. Results: The number of publications gradually increased from 2000 to 2021. The total citation count for the top 100 papers ranged from 15 to 433(mean = 67.43). The largest number of papers were published in 2016 (n=11). Meanwhile, USA (centrality: 0.93) and Columbia University (centrality: 0.06) were the most influential research country and institutions, respectively. The top contributing journals was Journal of Alzheimers Disease (8%). The IF for journals ranged from 1.819 to 53.44. A network analysis of the author's keywords showed that “beta” (centrality: 0.39), “amyloid beta” (centrality: 0.29), “hyperexcitability” (centrality: 0.29) and “disease” (centrality: 0.29) had a high degree of centrality. Conclusions: AD and epilepsy have been intensively studied in the past few years. The relationships, mechanisms and treatment of AD and epilepsy will be subjects of active research hotpots in future. These findings provide valuable information for clinicians and scientists to identify new perspectives with potential collaborators and cooperative countries.